Pemberdayaan Ekonomi Dayah sebagai Strategi Kemandirian Lembaga Pendidikan Islam - Suryani, Suryani; Hidayatullah, Syarif; Salabi, Agus Salim (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
This study aims to examine economic empowerment in dayahs as a strategy to increase the independence of Islamic educational institutions. The main problem faced is the dayah's dependence on external funding sources and the challenge of optimally managing local economic potential. The research used a qualitative approach with descriptive methods, involving in-depth interviews, participatory observation, and document analysis from various dayahs in Aceh.The results showed that economic empowerment of dayahs can be done through the development of productive business units, entrepreneurial skills training for santri, and utilization of local potential. This strategy not only supports the economic independence of dayahs, but also makes a real contribution to the welfare of the surrounding community. However, the implementation of economic empowerment in dayahs still faces obstacles such as limited human resources, overlapping regulations, and lack of access to modern technology. This research concludes that dayah economic empowerment is a strategic step that can transform dayahs into independent and competitive community-based economic centers. To overcome the existing challenges, an integrative approach and cross-sector collaboration are needed. Thus, dayahs can play a greater role not only as religious educational institutions, but also as the driving force of the local economy.